[n]‐Oligourea‐Based Green Sorbents with Enhanced CO2 Sorption Capacity. Issue 9 (20th April 2015) - Qaroush, Abdussalam K.; Castillo‐Molina, Dante A.; Troll, Carsten; Abu‐Daabes, Malyuba A.; Alsyouri, Hatem M.; Abu‐Surrah, Adnan S.; Rieger, Bernhard
Abstract A new series of [n]‐oligoureas ([n]‐OUs, n=4, 7, 10, and 12) green solid sorbents was prepared following a base‐catalyzed, microwave‐assisted oligomerization reaction. The materials were characterized by NMR and IR spectroscopy, elemental analysis, thermogravimetric analysis, differential scanning calorimetry, and XRD. Decomposition temperatures at 50 % weight loss (Td50) were ca. 350 °C for all oligomers. Urea and urethane functional groups indicated by IR spectroscopy confirmed the formation of the sorbent. The CO2 capturing capacities were determined at 35 °C and 1.0 bar (gravimetric method). Accordingly, [10]‐OU had the highest CO2 sorption capacity among the others (18.90 and 22.70 mg<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjm6shp63" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> CO 2</alternatives> gsorbent−1) at two different activation temperatures (60 or 100 °C, respectively). Chemisorption was the principal mechanism for CO2 capture. Cyclic CO2 sorption/desorption measurements were carried out to test the recyclability of [10]‐OU. Activating the sample at 60 °C, three stable CO2 sorption cycles were achieved after running the first cycle.